Algoritma Pemrograman Dalam Mengoperasikan Media Pembelajaran Laboratorium Virtual - Putri Hadiyatunnisa; Yahfizham (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
In using virtual laboratory media, programming algorithms are needed, so that students can use the media well. In this research, researchers want to know whether the virtual laboratory learning media for the food digestive system used in the learning process contains programming algorithms that are easy to understand or not. The research method used in this research is a qualitative approach. This virtual laboratory learning media contains programming algorithms that are easy to understand and use. Because it contains clear operating instructions in it. So that students can operate this virtual laboratory learning media well.